Efforts Made By PPKn Teachers in Dealing With Student Fighting - Faizan Manda Siregar (International Journal of Students Education, 2024)
This research aims to determine the efforts of PPKn teachers in dealing with brawls among students. This research uses the Literature review method where the data taken is excerpts of data from several articles and journals accessed from Google. The results of the research on the efforts of PPKn teachers in dealing with student brawls are seen from The aspects of teachers as guides and teachers as moral agents have been running well in accordance with their duties and responsibilities as teachers who guide students’ morals. Meanwhile, the factors that influence the occurrence of juvenile delinquency are caused by internal factors and external factors. Where lack of self-awareness, weak self-control and lack of parental attention, free association, social media, social environment causes juvenile delinquency.